2002
DOI: 10.1007/s00134-001-1190-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between early detection of soluble TNF-receptors and mortality in burn patients

Abstract: Early and progressive increase in sTNFR1 and sTNFR2 levels is associated with higher risk for poor outcome in severely burned patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The presented research is consistent with the results from other centres [18,33,34]. The highest sTNFR1 levels were recorded at the time of admission to the ED in the whole group of patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The presented research is consistent with the results from other centres [18,33,34]. The highest sTNFR1 levels were recorded at the time of admission to the ED in the whole group of patients.…”
Section: Discussionsupporting
confidence: 92%
“…Ribeiro et al [34] observed that the increase in sTNFR1 concentration negatively affected the prognosis of patients after burn injury. The authors of this study found that sTNFR1 concentrations were significantly elevated in both survivors and in the deceased, but statistically significant differences in sTNFR1 concentrations between groups were recorded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proinflammatory factors, such as tumor necrosis factor-α (TNF-α), C5a and leukotriene B4, chemoattractants (IL-8 and formyl-methionyl-leucyl-phenylalanine) and some growth factors (platelet-derived growth factor) were reported to be potent stimuli that upregulate the expression of CD11b [41][42][43]. Both clinical and experimental studies had demonstrated that numerous proinflammatory factors, such as TNF-α, IL-8 and C5a, could be induced by thermal injuries [25,[44][45][46]. So, the increased expression of CD11b on neutrophils and mono- Granulocytes were identified and gated by forward-and side-light scattering characteristics represented by MLFI using FACS assay.…”
Section: Discussionmentioning
confidence: 98%
“…92 In severely burned patients, an early increase in sTNF-RI and sTNF-RII was reported to be associated with a higher risk for poor outcome. 93 Major surgery resulted in elevated sTNF-RI and sTNF-RII expression and high sTNF-RII levels were associated with increased post-operative rates of mortality. 94,95 It was concluded that high levels of antagonists to TNF-α represented persisted activation of SIRS in critically ill patients.…”
Section: Markers Of Mediator Activitymentioning
confidence: 99%